Do technological and organizational innovation have significant influences on the logistics performance? - Zuraimi Abdul Aziz; Razli Che Razak; Mohd Rafi Yaacob; Nik Syuhailah Nik Hussin; Nurul Hasliza Mohd Razmin (International Journal of Business and Management Invention, 2016)
Logistics service providers (LSPs) need to engage with the innovation to achieve performance and keep their competitive advantage. LSPs are required to develop innovation in logistics activities to face challenges in the market. Logistics innovation can be considered as any type of associated service in logistics service. The purpose of this paper is to investigate the technological and organizational innovation as factors to measure the logistics performance of LSPs. Partial least square structural equation modeling (PLS-SEM) was conducted to examine relationship with logistics performance using SmartPLS 3 software. Technological innovation was found insignificant effect on logistics performance. The result of this study also indicated that organizational innovation has insignificant effects on logistics performance.